New scenarios for TV and audiovisual content in Peru and Latin America - Seminario Campos, Alejandro (2021)
Changes in audiovisual consumption in the last decade in Peru and in Latin America, may configure four future scenarios for the audiovisual medium, as explained by the Deloitte study on future scenarios for the television and video industry for 2030 In this sense, digitization has changed production processes and is allowing the consumption of multimedia content, which is increasingly flexible and mobile. Today the public no longer only reads, listens or watches the media, but also navigates, reacts and shares content, where the audiovisual shines as a star content in this new universe of the digital ecosystem.